Wi-Fi co-channel interference suppression approach in LTE uplink - Wan-zhi MA; Hong-zhi ZHAO; Hui-yue YU; Jun WANG; You-xi TANG (Tongxin xuebao)
Considering the Wi-Fi co-channel interference in the 3rd generation mobile communication long term evolution (LTE) uplink with multi-received antennas,a new combining approach named interference reconstruction rejection Combining was proposed.Firstly,as the covariance matrix approximation of the interference,the covariance matrix of the received signal was estimated.Secondly,the desired signal was reconstructed by interference rejection combining.Then,the interference was reconstructed by removing the desired signal.At last,the covariance matrix of the interference was estimated again for interference rejection combining.Simulation results over multipath fading channels show that the IRRC approach based on the minimum mean square error outperformed the conventional IRC approach about 2dB when the signal in LTE uplink is modulated by QPSK with 1 transmit antenna and 2 receive antennas,and the jam to signal ratio is 0dB.